PERCEIVED ORGANIZATIONAL SUPPORT AND LEADER-MEMBER EXCHANGE: A SOCIAL EXCHANGE PERSPECTIVE. - WAYNE, S. J.; SHORE, L. M.; LIDEN, R. C. (Academy of Management Journal, 1997)
Employees develop exchange relationships both with organizations and immediate superiors, as evidenced by research on perceived organizational support (POS) and leader-member exchange (LMX), respectively. Despite conceptual similarities between these two constructs, theoretical development and research has proceeded independently. In an attempt to integrate these literatures, we developed and tested a model of the antecedents and consequences of POS and LMX, based on social exchange theory. Results indicated that POS and LMX have unique antecedents and are differentially related to outcome variables, providing support for the importance of both types of exchanges.